Comparison of Fast Roll‐to‐Roll Flexographic, Inkjet, Flatbed, and Rotary Screen Printing of Metal Back Electrodes for Polymer Solar Cells1. Issue 10 (20th June 2013) - Hösel, Markus; Søndergaard, Roar R.; Angmo, Dechan; Krebs, Frederik C.
<x xml:space="preserve">Abstract</x> A comparison of the most promising silver back electrode manufacturing processes for polymer solar cells is presented. All printing methods are fully roll‐to‐roll (R2R) processed under ambient conditions with the same solar cell layer stack for better evaluation. This work delivers process recommendations and highlights challenges for each printing method to achieve good performing polymer solar cell modules and highly efficient device manufacturing. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>